Pictet–Spenglerases in alkaloid biosynthesis: Future applications in biocatalysis. (April 2020) - Roddan, Rebecca; Ward, John M.; Keep, Nicholas H.; Hailes, Helen C.
Abstract: Pictet–Spenglerases provide a key role in the biosynthesis of many biologically active alkaloids. There is increasing use of these biocatalysts as an alternative to traditional organic synthetic methods as they provide stereoselective and regioselective control under mild conditions. Products from these enzymes also contain privileged drug scaffolds (such as tetrahydroisoquinoline or β-carboline moieties), so there is interest in the characterization and use of these enzymes as versatile biocatalysts to synthesize analogs of the corresponding natural products for drug discovery. This review discusses all known Pictet–Spenglerase enzymes and their applications as biocatalysts.